Assessing Leadership Behaviour Using Modified Multifactor Leadership Questionnaire (MLQ) among Healthcare Managers Working at Government Health Agencies in Bangladesh (Bangladesh Journal of Medical Education, 2025)
Background: Assessing leadership behaviour has become more important than ever in recent years to enhance the managerial and leadership qualities of health managers to improve the capacity of healthcare delivery to the people of the country. Objective: To assess the leadership behaviour of healthcare managers working at two largest government agencies in health sector of Bangladesh. Materials & Methods: This cross-sectional study was conducted among 154 medical doctors working in different management positions, between January and December of 2023. Data were collected by face-to-face interview using modified Multifactor Leadership Questionnaire (MLQ). Four leadership styles (autocratic, democratic, transformational and laissez-faire) were assessed. 15 factors were taken into consideration; each factor had 3 associated questions. Using factor analysis, leadership behaviour was classified as high, moderate and low; low value was 0–4, while medium and high values were 5–8 and 9–12 respectively. Results: The mean age of the respondents was (43.25±8.387) years; 35.7% belonged to 41–50 years age group. 74.7% were male and 25.3% were female. Most of our study participants exhibited moderate levels of autocratic (66.2%) and laissez-faire (50.2%) leadership behaviour in their managerial roles. In contrast, they displayed high levels of democratic (96.8%) and transformational (93.5%) leadership behaviour. Through factor analysis, autocratic leadership behaviour was found at moderate levels among healthcare managers, while high levels of democratic and transformational and low levels of laissez-faire leadership behaviour were adopted by them. Conclusion: Healthcare managers must have clear understanding of various leadership styles to lead their organization towards highest level of quality health service. The results of this study may lead to development of necessary leadership education and training programmes for healthcare professionals of our country.BJME, Volume-16, Issue-02, July 2025: 115-121